4E analysis and multi-objective optimisation for a solar hybrid steam power plant using ABC algorithm: a case study in Iran. (27th January 2021) - Beyralvand, Davood; Yaghoubi, Mahmood
The objectives of this study are 4E analysis and multi-objective optimisation for solar hybrid fossil fuel power generation system and steam power plant without solar field (WSF) of Karaj during a year. The analysis is performed using MATLAB programing, and validated with a power plant unit data. The results show that system with oil-water heat exchanger (solar hybrid system), has less CO2 emission and fuel consumption than WSF power plant but 2.8% more exergy efficiency. The annual average contribution of steam on the production of electricity during sunny hours and during the day, are 15% and 7.3%, respectively. By using artificial bee colony (ABC) algorithm, system is optimised for maximum exergy efficiency and minimum cost of produced electricity. Furthermore, sensitivity analysis is performed to study the solar tracking modes, changing the number of collector loops, capacity of the power plant, interest rate and plant economic life on unit cost.